Simulation Marks (SimMarks) app: an approach to fix the coursework assessment gap problem among lecturers / Muhammad Farid Muhammad Fathullah ... [et al.] - Muhammad Fathullah, Muhammad Farid; Ismail, Siti Isma Hani; Zakariah, Zulfairul; Mohd Latib, Farah Wahida; Nazarudin, Ainamardia; Bachok, Mohd Fairuz (UiTM Press, 2024)
Nowadays in China, the English proficiency of non-English majors in universities and colleges, in general, is not as satisfactory as expected. One of the reasons is supposed to be the sharp decrease of English input during classroom time, compared with that in junior and senior high school. The research investigates whether monolingual teaching is a possible answer to the problem and the role of the monolingual classroom in improving students’ listening performance. The research is quantitative innature. It adopts a quasi-experimental design, with two classes of freshmen as participants, one being the experimental group, receiving monolingual teaching while the other is the control group, which receives traditional bilingual teaching. In each class, there are 40 students. Before and after the implementation of 15 weeks’ monolingual teaching, all the students have to take the pretest and posttest respectively. Besides, all the students have to take The Self-assessment Scales in China’s Standards of English Language Ability before and after the implementation of monolingual teaching to see whether they themselves consider their listening ability as having improved. Together with the interview on some students, the research finds that students’ listening performance in the experimental group does have a statistically significant improvement, compared with the control group and that L2 can help to change the class atmosphere and inspire students to learn English. The research serves as an empirical evidence for the effectiveness of monolingual teaching on students’ listening ability, as well as an indication for the direction in how to help the reform of foreign language teaching, especially English teaching in universities and colleges in China in the future.